Interview: An Intergenerational Dialogue on the Politics of Representation within Academia and Beyond - Aleman, Serjara; Moretti, Federica; Wiederkehr, Sara (Swiss Journal of Sociocultural Anthropology, 2025)
This interview is the edited excerpt of a dialogue recorded in the summer of 2023 between the three editors of this special feature and three experienced researchers: Prof. Susan Ossman, Dr. Eda Elif Tibet, and Dr. Nadine Wanono, who participated in a two-part CUSO module of the Swiss Graduate Program in Anthropology on Migration, Representation, and Reflexivity that the editors organized in 2020 and 2021. This interview is a follow-up of the conversations we initiated during the workshops, which constituted a florid ground to discuss past and present challenges in anthropology, as well as future developments of our anthropological practices.